Evaluation of silicon and salicylic acid for controlling basal stem rot disease on oil palm (Elaeis guineensis Jacq.) caused by Ganoderma boninense - Mohammad Seri, Ainnur Atira (2022)
Basal stem rot (BSR) disease, caused by Ganoderma boninense, is the most destructive disease that causes decay of the root system before ultimately rotting the lower stem of the oil palm (Elaies guineensis) which reduces the weight of fruit bunches. Repeated use of fungicides to control the disease develops fungal resistance and it is costly and environmentally unfriendly. The objectives of this study were to evaluate in vitro antifungal activity of salicylic acid (SA) and silicon (Si) in inhibiting mycelial growth of boninense and to evaluate the in vivo efficacy of Si treatment on the growth and oil palm seedlings resistance to G. boninense. For in vitro evaluation, 50, 100, 150, 200 and 250 mg/L of salicylic acid (SA), silicon dioxide (SiO2) and pure silicon (Si) were added individually to sterilized potato dextrose agar (PDA) to investigate the in vitro efficacy on the mycelial growth of Ganoderma boninense under laboratory conditions. The highest percentage inhibition of radial growth (PIRG) was observed for Si treatment followed by silicon dioxide (SiO2). Si treatment showed the highest percentage, 100% growth inhibition of boninense at concentration of 200 and 250 mg/L. Si can inhibit the mycelial growth of boninense significantly (p<0.05) at a lower concentration compared to SA and SiO2. The treatment also showed a significant difference compared to the other two treatments as even at a concentration of 100 mg/L, the Si treatment inhibited the mycelial growth of boninense better than the rest of the other treatments tested. There was a significant difference (p<0.05) in almost all concentrations tested for both Si and SiO2 except for PIRG at 200 and 250 mg/L which did not show a significant difference. The half maximal effective concentration (EC50) that inhibited mycelial growth of boninense was 68.57 mg/L, while for SiO2 and SA were 273.95 mg/L and 381.33 mg/L, respectively. For in vivo evaluation in the greenhouse, oil palm seedlings were pre-treated with 50, 100, 150, 200 and 250 mg/L of silicon (Si) respectively before being inoculated with Ganoderma boninense using the Dip, Place, and Drench (DPD) method and observed for five consecutive months. The group of inoculated seedlings that received no Si treatments were labelled as untreated control seedlings (UTC). Seedlings treated with Si showed a significant (p<0.05) reduction in disease severity against BSR where the concentrations of 150, 200 and 250 mg/L showed the lowest severity in leaf symptoms which were 7.36%, 6.49% and 4.05%, respectively with healthier and green leaves while the seedlings without Si showed the highest severity of leaf symptoms with multiple leaves turning yellow and dying. At five months after inoculation, examination of internal bole tissues of oil palm seedlings treated with Si at a concentration of 250 mg/L was the most effective in suppressing BSR and recorded a 3.0% mean percentage disease severity compared to other treatments as well as the untreated infected seedlings that showed 35.0% mean percentage disease severity. Si treatment plays an important role in keeping boninense infection below threshold by restricting the pathogen’s ability to penetrate host tissues.